Implementasi dan Tantangan Peran Teknologi pada Kontrak Hawalah dalam Sistem Perbankan Syariah - Auliah, Alvia `; Ningsih, Anggun Setya; Nuraliza Asrah, St.; Almadani, Futri Nur; Arsyad, Kamaruddin (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This study examines the implementation of technology in hawalah contracts at Indonesian Islamic banking institutions. Although financial technology (fintech) has developed rapidly, the integration of technology in hawalah products remains limited. This research analyzes technology implementation, identifies challenges, and evaluates the impact of technology on Sharia compliance. This study employs a qualitative approach with literature review method, analyzing secondary data from OJK regulations, Bank Indonesia, DSN-MUI fatwas, and scientific journals through systematic literature search with directed content analysis technique. The research findings indicate that technology implementation is dominated by electronic document management systems and online platforms. Main challenges include system integration complexity, data security, and variations in fiqh interpretation.